Erratum to: Bioactive layers based on black glasses on titanium substrates (Journal of the American Ceramic Society, (2018), 101, 2, (590-601), 10.1111/jace.15202) - Gaweda, Magdalena; Jelen, Piotr; Dlugon, Elzbieta; Wajda, Aleksandra; Lesniak, Magdalena; Simka, Wojciech; Sowa, Maciej; Detsch, Rainer; Boccaccini, Aldo R.; Sitarz, Maciej (Journal of the American Ceramic Society, 2018)
In the published article listed above, the last sentence of the Introduction should be changed from “To the best of our knowledge, there is no work devoted to the study of the bioactivity and biocompatibility of black glasses.” to the corrected version, which is “The bioactivity and cytocompatibility of silicon oxycarbide monoliths and powders have been investigated previously, however, to the best of our knowledge, there is no previous work devoted to the study of the bioactivity and biocompatibility of black glasses as coatings of titanium substrates.” In addition, the sentence should include citation of the reference “Gonzalo-Juan I, Detsch R, Mathur S, Ionescu E, Boccaccini AR, Riedel R. Synthesis and in vitro activity assessment of novel silicon oxycarbide-based bioactive glasses. Materials. 2016;9(12):959-969”.
CRIS-Team Scopus Importer:2022-08-05